An adaptive approach to service discovery in ad hoc networks - Augusto, Carlos Henrique Pereira (2006)
Service discovery allows the interaction between network nodes to cooperate in activities or to share resources in client-server, multi-layer, as well as in peer-to-peer architectures. Ad hoc networks pose a great challenge in the design of efficient mechanisms for service discovery. The lack of infrastructure along with node mobility makes it difficult to build robust, scalable and secure mechanisms for ad hoc networks. This paper proposes a scalable service discovery architecture based on directory nodes organized in an overlay network. In the proposed architecture, directory nodes are dynamically created with the aim of uniformly covering the entire network while decreasing the query latency for a service (QoS) and the number of control messages for the sake of increased scalability.